Oral Argumentation under Constraints: A Qualitative Study of Critical Thinking in Indonesian Higher Education - Gunawan; Sahril; Amirullah Abduh; Samtidar; Muhammad Jafar (Universitas Sulawesi Barat, 2026)
This study aims to explore the constraints that hinder the realization of critical thinking in students’ oral argumentation in higher education contexts. The study employed an interpretive qualitative case study design. The participants were four purposively selected lecturers who teach speaking courses emphasizing argumentative discussion at Universitas Muhammadiyah Bone. They had at least one semester of experience facilitating academic speaking activities and were selected through maximum variation sampling to capture diverse instructional perspectives. Data were collected through classroom observations, audio recordings of academic speaking activities, and interviews with lecturers. Thematic analysis was conducted iteratively to identify recurring linguistic, affective, and pedagogical constraints. The findings indicate that students’ oral argumentation is largely dominated by descriptive claims, with limited use of evidence, warrants, and rebuttals, revealing a gap between students’ critical thinking potential and their oral performance. This gap is affected by related language issues, like having a small vocabulary and not speaking smoothly; emotional factors, such as anxiety and fear of being judged; and teaching conditions, like not having enough training in argumentation and support for academic reading and writing. The study concludes that critical thinking in oral argumentation should be understood as a context-dependent and discursive practice rather than merely an individual cognitive ability. So, the research highlights the importance of teaching methods that combine language skills, emotional support, and clear training in argumentation to help improve critical thinking through speaking in higher education.